Functional Representations of SSA - Beringer, Lennart (SSA-based Compiler Design, 2022)
Functional programming languages provide a perspective on SSA that complements presentations based on phi-functions using notions such as nested scope, parameter passing, and mutually recursive function definitions. The correspondence extends from syntactic aspects to tasks such as SSA construction, data-flow analysis, and program transformations, and can be expressed in terms of multiple intermediate representation forms, all commonly found in compilers for functional programming languages. The chapter concludes with a discussion of loop nesting forests and their relationship to the relative placement of mutually recursive functions during block sinking and lambda dropping.